The Effect of Chief Executive Officer Demographics and Psychological Traits on Tax Aggressiveness in Indonesia - Anisa Kusumawardani; Anis Turmudhi; Noor Salim; Indri Widya Saputri (Universitas Negeri Semarang, 2025)
Purposes: This study examines the influence of Chief Executive Officer (CEO) characteristics on tax aggressiveness, framed within the Upper Echelon Theory, which emphasizes the role of top executives in shaping organizational outcomes. This research explores how CEO demographics and psychological traits such as gender diversity, generation, narcissism, facial masculinity, education, and nationality affect corporate tax behavior in Indonesia, addressing gaps in the literature on leadership traits and tax policy. Methods: The study employs quantitative methods, utilizing regression analysis on data collected from publicly listed companies in Indonesia to test the formulated hypotheses. Findings: The empirical results indicate that tax aggressiveness is significantly positively impacted by the CEO’s educational background, gender diversity, and face masculinity. According to the Upper Echelons Theory, these findings demonstrate how executive demographic and psychological characteristics influence business tax practices. In contrast, the data indicate that tax aggression is not substantially affected by narcissism, nationality, or generation of the CEO. These findings imply that all CEO features do not equally influence aggressive tax behavior and that certain traits may be more critical in strategic decision-making than others. Novelty: This study contributes to the literature by integrating psychological and demographic CEO traits in the context of corporate tax aggressiveness within the framework of upper-echelon theory as a grand theory, focusing on underexplored attributes like facial masculinity and narcissism. By situating the research within Indonesia, it addresses a significant gap in emerging market studies and provides actionable insights for leadership selection and tax compliance policies.